2004
DOI: 10.1038/modpathol.3800006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HER-2/neu amplification in endometrial carcinoma by chromogenic in situ hybridization. Correlation with fluorescence in situ hybridization, HER-2/neu, p53 and Ki-67 protein expression, and outcome

Abstract: Fluorescence in situ hybridization (FISH) is the most widely used technique to detect HER-2/neu gene amplification; however, it is only available in some institutions. In contrast, chromogenic in situ hybridization (CISH) can be evaluated by routine light microscopy. In endometrial carcinoma there are few data concerning HER-2/neu status and prognosis. Therefore, we determined HER-2/neu gene status by CISH using a digoxigenin-labelled probe on 60 formalin-fixed paraffin-embedded endometrial carcinomas. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
3
44
0
1
Order By: Relevance
“…These findings are consistent with the results of previous studies, which have shown concordance rates between CISH and FISH and/or immunohistochemistry to be in the range of 90-100%. [15][16][17][18][19][20][21] A recent study by Gong et al 21 evaluated the HER2 status of 80 archival invasive breast carcinoma specimens by CISH and FISH, and also assessed the interobserver reproducibility of CISH results between three pathologists. A 91% agreement in CISH results between pathologists was reported and all these cases had HER2 status matching the corresponding FISH results.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of previous studies, which have shown concordance rates between CISH and FISH and/or immunohistochemistry to be in the range of 90-100%. [15][16][17][18][19][20][21] A recent study by Gong et al 21 evaluated the HER2 status of 80 archival invasive breast carcinoma specimens by CISH and FISH, and also assessed the interobserver reproducibility of CISH results between three pathologists. A 91% agreement in CISH results between pathologists was reported and all these cases had HER2 status matching the corresponding FISH results.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Many other studies also included various histological subtypes and grades of endometrial carcinoma, and even malignant mixed mullerian tumors (carcinosarcomas) in the HER2 testing of endometrial serous carcinoma same analysis, making the interpretation of data difficult. [14][15][16]34,35 Several previous studies used non-FDA-approved HER2 antibodies, ie, c-erbB-2 clone A0485 (DAKO), 24,35,36 c-erbB-2/ Her-2/neu Ab17 (monoclonal antibodies e2-4001 and 3B5; Neomarkers) 8 and clone TAB250 (Zymed). 16,35 Although most studies used the FDA scoring criteria for HER2 immunohistochemistry, 8,9,[13][14][15]18,22,24,30,35,36 many of them considered both the 2 þ and 3 þ immunohistochemical scores positive for HER2 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16]34,35 Several previous studies used non-FDA-approved HER2 antibodies, ie, c-erbB-2 clone A0485 (DAKO), 24,35,36 c-erbB-2/ Her-2/neu Ab17 (monoclonal antibodies e2-4001 and 3B5; Neomarkers) 8 and clone TAB250 (Zymed). 16,35 Although most studies used the FDA scoring criteria for HER2 immunohistochemistry, 8,9,[13][14][15]18,22,24,30,35,36 many of them considered both the 2 þ and 3 þ immunohistochemical scores positive for HER2 overexpression. 8,13,15,30,35,36 Others used selfdeveloped semiquantitative immunohistochemical scoring systems, not currently approved for any other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…25 Overexpression of Her-2/neu is present in a variety of carcinomas, including those of the breast, bladder, ovary, endometrium, and lung, and is generally associated with a poor prognosis. [26][27][28][29] Recently, Montironi et al 30 found that Her-2/neu is overexpressed in androgen independent prostate cancer and is not associated with gene amplification. In our study, Her-2/neu staining was not present in any of the stromal components, and this protein was only weakly expressed in the epithelial components in some cases.…”
Section: Discussionmentioning
confidence: 99%